PENERAPAN PERILAKU HIDUP SEHAT MELALUI PENYULUHAN PHBS DI DESA LEBAH SEMPAGA KECAMATAN NARMADA - Hasdiawan, Ziyad Marta; Nisa, Khairun; Arni, Ginanda Azahra Va; Abidin, M.Zaenal; Nurmajidah, Nurmajidah; Diantina, Jantisa; Erminati, Riri; Azizzah, Wafiqoh Nurul; Yuliani, Yuliani; Rahmadhani, Zurlina; Nurkamfajriani, Nurkamfajriani (Jurnal Wicara, 2023)
PHBS Counseling activities were carried out by Integrated KKN Students in Lebah Sempaga Village, Narmada District, West Lombok Regency. This service aims to increase the knowledge, ability, awareness, and willingness of all school members and the community in Lebah Sempaga Village to adopt a clean and healthy life. The problem of clean and healthy living among school residents and the Lebah Sempaga village community can be achieved by changing unhealthy behavior into healthy behavior and creating a healthy environment. Providing education through counseling is one way that can be done to make school members and the community aware of the importance of clean and healthy living behaviors. The implementation of clean and healthy lifestyle (PHBS) counseling activities was carried out in two places. First, PHBS counseling activities in hamlets. Second, PHBS counseling activities at SD Negeri 1 Lebah Sempaga. The result of these counseling activities is an increase in the knowledge, ability, awareness, and willingness of residents in the school environment and in the community to implement clean and healthy living behaviors.